MODEL FRAYER UNTUK PENGUASAAN KOSAKATA SISWA SEKOLAH DASAR - Octavian Muning Sayekti (Universitas Sarjanawiyata Tamansiswa, 2015)
Abstrak: If we want to learn one language, one should know the target of the vocabulary it’s self. If they have much vocabulary, they will be more skillful in languages. Learning vocabulary at school, it’s better to apply the strategy of the learning. This purpose is in order the students is understood and interested in learning vocabulary. One of the learning strategy alternative vocabulary, that is frayer model. Frayer model is one learning strategy that used grafic in the learning proces . In this case, it will make students easier to know the concept of a vocabulary.